Intravenous Administration of Endothelial Colony-Forming Cells Overexpressing Integrin β1 Augments Angiogenesis in Ischemic Legs. (23rd December 2015) - Goto, Kazuko; Takemura, Genzou; Takahashi, Tomoyuki; Okada, Hideshi; Kanamori, Hiromitsu; Kawamura, Itta; Watanabe, Takatomo; Morishita, Kentaro; Tsujimoto, Akiko; Miyazaki, Nagisa; Ushikoshi, Hiroaki; Kawasaki, Masanori; et al.
Abstract : The reparative capacity of endothelial progenitor cells appears to be limited by their poor survival when injected directly into ischemic tissue. Human endothelial colony-forming cells (ECFCs) were transduced using a lentiviral vector encoding integrin β1 (ITGB1) or enhanced green fluorescent protein. Blood perfusion of the ischemic limb was significantly augmented only in the ITGB1-ECFC group. Intravenous administration of ECFCs engineered to home to ischemic tissue appears to efficiently mediate therapeutic angiogenesis. Abstract: : When injected directly into ischemic tissue in patients with peripheral artery disease, the reparative capacity of endothelial progenitor cells (EPCs) appears to be limited by their poor survival. We, therefore, attempted to improve the survival of transplanted EPCs through intravenous injection and gene modification. We anticipated that overexpression of integrin β1 will enable injected EPCs to home to ischemic tissue, which abundantly express extracellular matrix proteins, the ligands for integrins. In addition, integrin β1 has an independent angiogenesis-stimulating function. Human endothelial colony-forming cells (ECFCs; late-outgrowth EPCs) were transduced using a lentiviral vector encoding integrin β1 (ITGB1) or enhanced green fluorescent protein (GFP). We then locally or systemically injected phosphate-buffered saline or the genetically modified ECFCs (GFP-ECFCs or ITGB1-ECFCs; 1 × 10 5 cells each) into NOD/Shi-scid, IL-2Rγnull mice whose right femoral arteries had been occluded 24 hours earlier. Upregulation of extracellular matrix proteins, including fibronectin, was apparent in the ischemic legs. Four weeks later, blood perfusion of the ischemic limb was significantly augmented only in the ITGB1-ECFC group. Scanning electron microscopy of vascular casts revealed increases in the perfused blood vessels in the ischemic legs of mice in the ITGB1-ECFC group and significant increases in the density of both capillaries and arterioles. Transplanted ECFC-derived vessels accounted for 28% ± 4.2% of the vessels in the ITGB1-ECFC group, with no cell fusion. Intravenous administration of ECFCs engineered to home to ischemic tissue appears to efficiently mediate therapeutic angiogenesis in a mouse model of peripheral artery disease. Significance: The intravenous administration of endothelial colony-forming cells (ECFCs) genetically modified to overexpress integrin β1 effectively stimulated angiogenesis in ischemic mouse hindlimbs. Transplanted ECFCs were observed in the ischemic leg tissue, even at the chronic stage. Moreover, the cells appeared functional, as evidenced by the improved blood flow. The cell type used (ECFCs), the route of administration (intravenous, not directly injected into the affected area), and the use of ligand-receptor interactions (extracellular matrix and integrins) for homing represent substantial advantages over previously reported cell therapies for the treatment of peripheral artery disease.